The application of new product development principles in the pharmaceutical industry : a comparative study of marketing practitioners' perceptions - Venter, Gertruida Helena Christina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2001.